2018
DOI: 10.1016/j.rmcr.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary contusion after bumper car collision: Case report and review of the literature

Abstract: Thoracic trauma is a major source of morbi-mortality in injured children. Their pliable chest wall makes pulmonary contusion the most common chest injury. It is most often secondary to blunt trauma caused by traffic accidents. We report a case of severe chest trauma caused by a bumper car collision in an 8-years old girl. She sustained right lung contusion that led to complete atelectasis. After a week of supportive therapy, bronchoscopy removed a mucous plug from the main bronchus, resulting in significant cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that patients that underwent open reduction and internal fixation experienced a significant reduction of chest pain and an effective recovery of cough, which aids expectoration [20][21][22]. For these patients, getting out of bed early in the postoperative period not only promoted recovery but reduced the incidence of atelectasis.…”
Section: The Necessity Of Surgical Treatmentmentioning
confidence: 99%
“…Previous studies have demonstrated that patients that underwent open reduction and internal fixation experienced a significant reduction of chest pain and an effective recovery of cough, which aids expectoration [20][21][22]. For these patients, getting out of bed early in the postoperative period not only promoted recovery but reduced the incidence of atelectasis.…”
Section: The Necessity Of Surgical Treatmentmentioning
confidence: 99%
“…Surfactants normally decrease the surface tension of alveoli 19 . If there is for some reason reduction in the amount of active surfactant, it leads to pulmonary atelectasis and ventilation‐perfusion mismatch 2,20 . Patients with traumatic ARDS have a higher risk of pneumonia and respiratory failure than those without pulmonary contusions 3,7,11,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“… 19 If there is for some reason reduction in the amount of active surfactant, it leads to pulmonary atelectasis and ventilation‐perfusion mismatch. 2 , 20 Patients with traumatic ARDS have a higher risk of pneumonia and respiratory failure than those without pulmonary contusions. 3 , 7 , 11 , 15 , 16 Another difference from ARDS caused by infection or aspiration is that patients with ARDS secondary to trauma are usually younger and effective interventions at an early stage of onset can lead to better outcomes and good patient prognosis.…”
Section: Introductionmentioning
confidence: 99%